A critical review of the physiological, ecological, physical and chemical factors influencing the microbial degradation of concrete by fungi. (15th April 2022) - Jiang, Liying; Pettitt, Tim R.; Buenfeld, Nick; Smith, Stephen R.
Abstract: Concrete is the most extensively used material in construction and is generally relatively resistant, but under certain environmental conditions it is susceptible to microbially influenced degradation (MID) by bacteria, algae and fungi. Filamentous fungi, including Fusarium oxysporum, Aspergillus niger and Cladosporium sphaerospermum, are widely detected on corroded concrete surfaces. However, in contrast to bacteria, the extent of, and factors influencing, fungal influenced degradation (FID) of concrete are poorly understood. The extensive presence and survival ability of fungi in concrete may be explained by their remarkable environmental adaptability and capacity to modify potentially extreme environments, including alkaline pH conditions found in concrete, facilitating its exploitation by, and growth of, the organism. Furthermore, fungi produce dormant, resistant spores that remain viable and survive for long periods of time, cellular autolysis conserves resources to maintain viability and growth in low nutrient conditions, and the mycelial network facilitates the transport of nutrients, substrates, water and oxygen (O2 ) within fungal colonies. The concrete environment is rich in calcium (Ca), which is essential for hyphal growth, and the requirement for this important nutrient may explain why fungi grow in and exploit concrete as a resource. The identified mechanisms responsible for the FID of concrete, include: (1) the formation and leaching of soluble Ca salts from the reaction of organic acids secreted by fungal cells with Ca in concrete; (2) expansion due to formation of insoluble Ca salts, such as Ca citrate, from the reaction with fungal organic acids; (3) crack development by ettringite formation from the secretion of the enzyme, keratinase, and amino acids; and (4) potential mechanical attack by fungal hyphal growth and extension into solubilisation zones and cracks. The mechanisms of FID operate simultaneously and potentially have important, yet currently underestimated, consequences for the aesthetic, functional and structural properties of concrete structures. However, direct evidence of internal decay induced by fungal hyphae is lacking, and physical and chemical research is required to demonstrate the potential extent and significance of internal FID of concrete. Highlights: Fungi survive and grow in concrete by modifying the local environment. Fungal influenced degradation of concrete is driven primarily by organic acid chemical attack. Fungi secrete keratinase and amino acids, accelerating concrete cracking. Fungi may attack concrete mechanically due to hyphal penetration.